The Development of Acute Outreach Services in Aged Care Facilities (Nursing Homes): Using Telemedicine in Rural Areas - Daniel Kam Yin Chan (Aging Medicine)
Acute outreach services for older patients in nursing homes are being developed as our population ages rapidly, putting stress on the resources of hospitals and emergency departments. Since the COVID pandemic, the acceleration of the utilization of telemedicine has also been adopted for acute outreach services in metropolitan areas, with preliminary evidence supporting safety, but the generalization of the service to other settings, such as rural areas, is less clear.